2005
DOI: 10.1074/jbc.m412006200
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Rat Inositol Polyphosphate Kinases rIPK2 and rIPK1 in Inositol Pentakisphosphate and Inositol Hexakisphosphate Production in Rat-1 Cells

Abstract: Over 30 inositol polyphosphates are known to exist in mammalian cells; however, the majority of them have uncharacterized functions. In this study we investigated the molecular basis of synthesis of highly phosphorylated inositol polyphosphates (such as inositol tetrakisphosphate, inositol pentakisphosphate (IP 5 ), and inositol hexakisphosphate (IP 6 )) in rat cells. We report that heterologous expression of rat inositol polyphosphate kinases rIPK2, a dual specificity inositol trisphosphate/inositol tetrakisp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 51 publications
4
42
0
Order By: Relevance
“…In the absence of stimulation by Wnt3a, cells display little change in intracellular IP 3 or IP 5 levels when IPMK is suppressed by siRNA. Earlier studies report dramatic reductions in IP 5 accu- mulation in HEK293 and HeLa cells (45), as well as in Rat-1 cells (38), when IPMK expression was suppressed with siRNA. Unlike these earlier studies performed with serum-fed cells, our studies required that we eliminate serum to study the Wnt response, likely the basis for the differences in the effects observed in response to IPMK suppression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of stimulation by Wnt3a, cells display little change in intracellular IP 3 or IP 5 levels when IPMK is suppressed by siRNA. Earlier studies report dramatic reductions in IP 5 accu- mulation in HEK293 and HeLa cells (45), as well as in Rat-1 cells (38), when IPMK expression was suppressed with siRNA. Unlike these earlier studies performed with serum-fed cells, our studies required that we eliminate serum to study the Wnt response, likely the basis for the differences in the effects observed in response to IPMK suppression.…”
Section: Resultsmentioning
confidence: 99%
“…4A) (37)(38)(39)(40)(41)(42). Aurintricarboxylic acid (ATA, 2 M) has been shown in vitro to inhibit IP3K and IPMK; whereas adriamycin (20 M) has been shown in vitro to inhibit IP3K and CGA (40 M) has been shown in vitro to inhibit IPMK (43,44).…”
Section: Resultsmentioning
confidence: 99%
“…However, the extent to which ITPK1 contributes to higher order inositol phosphate synthesis in mammals remains to be demonstrated in a range of conditions and cell types. For example, it has been shown that two other inositol kinases, IPK1 and IPK2, are sufficient to recapitulate InsP 6 synthesis from Ins(1,4,5)P 3 (38,39). In contrast, the function of gmITPK4 in soybean is likely restricted to the synthesis of higher inositol polyphosphates.…”
Section: )P 3 Does Not Stimulate Thismentioning
confidence: 99%
“…The cDNA for human G␣ q QL in pcDNA was from UMR cDNA Resource Center (Rolla, MO). The construction of the rat IPMK cDNA construct pBabePuro-GFP-rIPMK was described previously (57). The human Vip1 kinase domain (residues 1-387) CFP fusion construct pmCFPhsVIP1-KD has been described (27).…”
Section: Methodsmentioning
confidence: 99%